Organizing Traditional Folk Games Committee for the August 17th Event in Kolam Village - Agnes Monica Hutahaean; Rifaldo P. Simbolon; Dedi Torman Gea; Nurfadillah Siregar (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: Indonesia's Independence Day on August 17th is traditionally celebrated with folk games (permainan rakyat) that foster community spirit and preserve cultural heritage. Kolam Village required organized committee support to successfully implement these traditional sporting activities, addressing limited organizational capacity and declining youth participation in cultural events. This community service aimed to establish an effective organizing committee (kepanitiaan) for traditional folk games during the August 17th celebration, enhance community participation, preserve cultural heritage, and strengthen social cohesion among villagers. Methods: The program was implemented through participatory approaches including committee formation and training, event planning workshops, and direct facilitation of traditional games such as balap karung (sack race), tarik tambang (tug-of-war), makan kerupuk (cracker eating contest), and balap bakiak (wooden clog race). Implementation occurred over three months with pre-event preparation, execution, and post-event evaluation phases. Results: The program successfully engaged 250+ participants across all age groups, with 87% satisfaction rate among community members. The organizing committee effectively coordinated 8 traditional game categories, mobilized 45 volunteers, and demonstrated improved organizational capacity evidenced by enhanced time management, resource allocation, and community mobilization skills. Conclusion: The initiative strengthened community bonds, revived cultural traditions among youth, and established a sustainable model for future community events, with the organizing committee expressing commitment to continue annual celebrations.